Aklatang Pambata strengthening reading habits of children - De Dios, Pleasant C.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
In the Philippines, the establishment of public libraries in every community is government-mandated, yet developing the reading habits among children remains a difficult endeavor. Aside from the lack of funding, libraries must face the challenge of overturning a non-reading culture that is prevalent in poor communities. Aklatang Pambata, which is relatively a new library, has relied mainly on donations to jumpstart and maintain library operations, with little or no help from the government. After continually promoting itself to the community, the library now has an impressive number of library patrons, especially during weekend activities. However, it was observed that not all children visit the library to read, and mostly play with other children and leave the book unnoticed. The purpose of this paper was to understand why children liked coming to the library without an interest in reading, despite the library's attempts to promote reading among children.
After the study, it was found that lack of consistency with implementing rules and regulation inside the library encouraged ill conduct, and the library orientation was not regularly provided in the school, to teach young children proper behavior. The role of the library in developing the reading habit in children could not be fully realized because the children's exposure to books is limited to their exposure to the library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Books and reading -- Philippines -- Quezon City; Children's libraries -- Philippines -- Quezon City